2001
DOI: 10.3109/15419060109080703
|View full text |Cite
|
Sign up to set email alerts
|

Rac Regulates Vascular Endothelial Growth Factor Stimulated Motility

Abstract: During angiogenesis endothelial cells migrate towards a chemotactic stimulus. Understanding the mechanism of endothelial cell migration is critical to the therapeutic manipulation of angiogenesis and ultimately cancer prevention. Vascular endothelial growth factor (VEGF) is a potent chemotactic stimulus of endothelial cells during angiogenesis. The endothelial cell signal transduction pathway of VEGF represents a potential target for cancer therapy, but the mechanisms of post-receptor signal transduction inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
58
1
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(63 citation statements)
references
References 55 publications
(56 reference statements)
3
58
1
1
Order By: Relevance
“…Though several studies showed that VEGF causes endothelial cell migration by inducing Rac1-stimulated lamellipodia formation, the pathway between VEGF signaling and Rac1 activation was not explored [4]. In this study, we identified the exchange factor Vav2 as mediating VEGF signaling to Rac1.…”
Section: Discussionmentioning
confidence: 89%
See 3 more Smart Citations
“…Though several studies showed that VEGF causes endothelial cell migration by inducing Rac1-stimulated lamellipodia formation, the pathway between VEGF signaling and Rac1 activation was not explored [4]. In this study, we identified the exchange factor Vav2 as mediating VEGF signaling to Rac1.…”
Section: Discussionmentioning
confidence: 89%
“…Previous work has shown that VEGF stimulates HUVEC migration [4,5,36]. Since our findings suggested that Vav2 specifically activates Rac1 during VEGF signaling, we investigated whether Vav2 was required for the migration of HUVECs and HMVEC-d towards VEGF.…”
Section: Vav2 Is Necessary For Vegf-induced Endothelial Cell Migrationmentioning
confidence: 92%
See 2 more Smart Citations
“…The dysregulated Rac1 activity has been implicated in several aspects of malignant phenotypes such as tumorigenic transformation and outgrowth (21)(22)(23)(24)(25). Rac1 is also integral in the regulation of tumor angiogenesis through its control over epithelial cell motility (26)(27)(28) and endothelial cell permeability (29,30). We (6)(7)(8) and others (31)(32)(33)(34) have shown that Rac1 activity contributes to the resistance of cancer cells to apoptosis by different chemotherapies.…”
Section: Introductionmentioning
confidence: 99%